Circuit Learning Model Based "Akidah" In Modified Volleyball For Elementary School Students - Pungki Indarto; Gatot Jariono; Muhammad Faiz; Rafli Muhammad; Dwi Endri Mei Minawati (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2021)
This development research resulted in a circuit learning model based on AKIDAH in modified volleyball games in elementary schools. This model is packaged in circuit form. The purpose of this research is to develop a learning model in accordance with the characteristics of elementary school students.  The samples in this study were students of SD Muhammadiyah Special Program Baturan, Griyan Baturan Colomadu with a sample of research is grade 4 and 5 students numbering 40 people using pruposive sampling technique. The method used was the development research of Borg and Gall. The data collection instruments used were questionnarires, and mini volleyball game test instruments, while data analysis used qualitative and quantitative descriptions. The stages of this research are (1) needs analysis; (2) development; (3) small group trials; (4) The product effectiveness test uses the skills of playing modified volleyball with the results obtained using the skills of serving, passing, and smash. The results showed that the expert validation of the learning model was 75.5% very valid. 76.2% material expert analysis very valid categories. The test results are moderate in 35 categories. Overall the analysis of the 82.6 model with the category deserves a good predicate.